Distribution Genotype High Risk (HR) And Low Risk (LR) Human Papillomavirus (HPV) at Condyloma Acuminata - Gondo Mastutik; Alphania Rahniayu; Dwi Murtiastutik; Afria Arista; Trisniartami Setyaningrum; Nabiha Missaoui; Suhartono Taat Putra (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2021)
Introduction: Condyloma acuminata that is also known as genital warts are one of the most common sexually transmitted that caused by infection of Human papillomavirus (HPV). Persistent infection of Low Risk (LR) or High risk (HR) HPV is a risk factor for progress into benign or malignant cancer. The objective is to analyze distribution of genotype LR-HPV and HR-HPV at condyloma acuminata in anogenital region. Methods: A cross sectional study using were 36 lesions from men and women of condyloma acuminata patients. All subject signed the informed consent and ethic obtained from our institution, number 382/Panke.KKE/V/2016. The specimen was used to histopathological examination and to identified 40 genotypes of HPV using a reverse line blot assay.Results: The All patients were diagnosed as condyloma acuminata, some with focus dysplasia and koilocytosis. All patients were positive for HPV, including LR-HPV were HPV 6, 11, 42, 54, 61, 81,87,89 and HR-HPV were HPV 18, 26, 45, 51, 52, 66, 67, 68B, 69, 82. The single infection of LR-HPV was 44.4%, multiple infection LR/LR-HPV was 13,9% and the multiple infection of LR/HR-HPV was 41.7%. The LR-HPV infected 70,6% and HR-HPV infected 29,4%. Conclusion: LR-HPV is the major infection of condyloma acuminata, in single infection or multiple infection with HR-HPV. The most common infections were HPV 11, followed by HPV 6, HPV 18, HPV 51, and HPV 82. The determination of genotype of HPV can be used to predict the malignant transformation.